Synthesis of Novel α‐Aminophosphonate Derivatives, Biological Evaluation as Potent Antiproliferative Agents and Molecular Docking. Issue 20 (28th May 2018) - Deshmukh, Satish U.; Kharat, Kiran R.; Yadav, Ashok R.; Shisodia, Suresh U.; Damale, Manoj G.; Sangshetti, Jaiprakash N.; Pawar, Rajendra P.
Abstract: A series of novel fluorine containing α‐aminophosphonate derivatives (4 a–4 q ) were synthesized in excellent yield and high purity. All these novel Fluorinated α‐aminophosphonate compounds were screened for antiproliferative and apoptosis activity on human non small cell lung carcinoma cells (A549) and human skin melanoma cells (SK‐MEL‐2). Compounds4 a, 4 b, 4 c, 4 f, 4 i, 4 j and4 m were found to be more active antiproliferative agent against A549 and SK‐MEL‐2 cells with IC50 value 0.22 to 1.25 μM. Molecular docking study related to binding affinity and binding mode analysis showed that synthesized compounds had potential to inhibit human Topoisomerase IIa enzyme system. Flow cytometric study showed some of these derivatives also induced cell apoptosis and arrest cell cycle at G1 and at G2 /M phase. Overall, this study provides future perspective of lead candidate for the future anticancer drug discovery initiatives. Abstract : A series of novel fluorine containing α‐aminophosphonate derivatives (4 a–4 q) were synthesized in excellent yield and high purity. All these novel Fluorinated α‐aminophosphonate compounds were screened for antiproliferative and apoptosis activity on human non small cell lung carcinoma cells. Flow cytometric study showed some of these derivatives also induced cell apoptosis and arrest cell cycle at G1 and at G2 /M phase. Overall, this study provides future perspective of lead candidate for the future anticancer drug discovery initiative.